2018
DOI: 10.1186/s12943-018-0893-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression signatures of exosomal long non-coding RNAs in urine serve as novel non-invasive biomarkers for diagnosis and recurrence prediction of bladder cancer

Abstract: Recently, expression signatures of exosomal long non-coding RNAs (lncRNAs) have been proposed as potential non-invasive biomarkers for cancer detection. In this study, we aimed to develop a urinary exosome (UE)-derived lncRNA panel for diagnosis and recurrence prediction of bladder cancer (BC). Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to screen and evaluate the expressions of eight candidate lncRNAs in a training set (208 urine samples) and a validation set (160 urine samples). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
170
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 9 publications
(8 reference statements)
4
170
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are an important group of transcribed RNA molecules that have a length greater than 200 nucleotides [13]. The rapid development of RNA genomics has highlighted the role of lncRNAs in many human diseases, especially in cancers [14][15][16][17][18][19]. Recent accumulating evidence has indicated that lncRNAs, such as BLACAT2, UCA-1, LNMAT1 and PANDAR, play important regulatory roles in diverse biological processes in bladder cancer [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are an important group of transcribed RNA molecules that have a length greater than 200 nucleotides [13]. The rapid development of RNA genomics has highlighted the role of lncRNAs in many human diseases, especially in cancers [14][15][16][17][18][19]. Recent accumulating evidence has indicated that lncRNAs, such as BLACAT2, UCA-1, LNMAT1 and PANDAR, play important regulatory roles in diverse biological processes in bladder cancer [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that long noncoding RNAs (lncRNAs) can be expressed in exosomes derived from tumor serum, cells, and microenvironment . Studies have shown that serum and urine exosome lncRNA can be used as biomarkers for the diagnosis and prognosis of BC . In addition, exosomal lncRNA is also involved in the regulation of BC development .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal lncRNAs can be also isolated from other body fluids rather than the most common, such as plasma or serum. For instance, Zhan et al [35] validated a panel of three lncRNAs (MALAT1, PCAT-1 and SPRY4-IT1) by RT-qPCR, in urine exosomes (UE) of 80 bladder cancer patients and 80 healthy controls, and found a significant overexpression in bladder cancer patients. The verification of the diagnostic capacity indicated a much better performance for this panel than for the urine cytology, which is widely used in clinical practice.…”
Section: Clinical Value Of Using Exosomal Lncrnas As Liquid Biopsiesmentioning
confidence: 99%